Alcohol dehydration performance of pervaporation composite membranes with reduced graphene oxide and graphene quantum dots homostructured filler. (June 2020) - Lecaros, Rumwald Leo G.; Bismonte, Ma. Elizabeth; Doma, Bonifacio T.; Hung, Wei-Song; Hu, Chien-Chieh; Tsai, Hui-An; Huang, Shu-Hsien; Lee, Kueir-Rarn; Lai, Juin-Yih
Abstract: Graphene quantum dots(GQDs) were used to possibly cover the structural defects on the graphitic regions of reduced graphene oxide(rGO). The resulting homostructure nanocomposite fillers(rGO + GQD) were incorporated in an alginate solution creating a dense composite membrane for pervaporation. The membranes were applied to separate alcohol/water mixtures in which the successful covering of structural defects was observed with good separation performance of lower molecular weight alcohols. The Raman spectra and elemental analyses confirmed the successful changes on the physical and chemical structures of the homostructured fillers. The X-ray diffraction pattern showed that the crystallinity of the membrane was greatly affected when incorporated with rGO + GQD. The alginate incorporated with 3 wt% of rGO + GQD(Alg-rGO + GQD) has the best pervaporation performance in separating methanol/water mixture with a permeation flux of 2323 g m −2 h −1 and water concentration in permeate of 92.7% at 70 °C. While the positron annihilation lifetime spectroscopy results supported that the minimization of the structural defects enhanced the water selectivity of the membrane by easy transport of water molecules through the free volume spaces and blocks methanol molecules. The results in this study may provide the possible sealing or curing the defects on rGO with GQDs and improve the interfacial interaction with the polymer matrix. Graphical abstract: The successful sealing or curing of structural defects on rGO with GQDs blocks the transport of alcohol molecules and only allow water molecules. Image 1